Making Mathematics Memorable, Meaningful, and Fun: Activities to Enhance Precalculus - (:unkn) unknown (My University, 2015)
To master material, students need to make it their own. As teachers, we should structure their interactions with mathematics in ways that are memorable, meaningful, and fun. One way to do this is to provide activities that stretch beyond the textbook and lead students to think and talk to one another about mathematics. This thesis contains a set of activities designed to enhance a precalculus course, along with solutions and feedback on each activity.